Andreas Gursky - Andreas Gursky; Peter Galessi (NY; MoMA, 2011)
The big, bold, seductive and surprising color photographs of German photographer Andreas Gursky set forth a stunning image of our contemporary world of high-tech industry, international markets, big-time sports, fast-paced tourism and slick commerce. Tracking the zeitgeist from his native Germany to such far-flung places as Hong Kong, Brasilia, Cairo, New York, Shanghai, Stockholm, Tokyo, Paris, Singapore and Los Angeles, Gursky has earned acclaim at the leading edge of contemporary art with a polished signature style that draws upon a great diversity of ideas, precedents and techniques. Created in collaboration with the artist, this oversize book surveys the fullness of his work to date with gorgeous color plates, generous two-page details, and a wealth of supporting illustrations. The first in-depth study in English of Gursky's art, this book was published in conjunction with a major retrospective at The Museum of Modern Art, New York.
German
Keywords: 21st century; N4390-5098 Visual Arts. Exhibitions; Germany